Preliminary study on the correlation between thyroid magnetic resonance parameters and radiation dose after radiotherapy for nasopharyngeal carcinoma - Kuan Lu; Chenxia Zhou; Jiaming Ren; Jialu Ni; Weisen Yang; Yeqing Wang; Dan Jin; Jianjun Qian; Yaqun Zhu; Dai Shi; Wentao Hu; Liang Xu (Frontiers in Public Health)
BackgroundHypothyroidism is a common sequela after radiotherapy for nasopharyngeal carcinoma (NPC). Magnetic resonance imaging (MRI) has gained prominence in thyroid imaging, leveraging its non-ionizing radiation, high spatial resolution, multiparameter and multidirectional imaging. Few previous studies have investigated the evaluation of radiation-induced thyroid injury by MRI.MethodsMRI and radiotherapy data of 32 patients who were first diagnosed with nasopharyngeal carcinoma in our hospital from April 2015 to April 2024 and underwent radiotherapy in the radiotherapy department were retrospectively collected. Before, during and after radiotherapy, the thyroid morphology was observed on MR images, and the quantitative parameters of size (width, thickness) were measured on T1-weighted images. The signal intensity (SI) of the thyroid gland was measured on T1-weighted imaging (T1WI), T2-weighted imaging (T2WI) and contrast-enhanced T1-weighted imaging. The differences in thyroid parameters at different time points before and after radiotherapy were compared. The correlation between the MRI quantitative parameters of the thyroid and the radiation dose volume of the thyroid and the radiation dose of the pituitary were analyzed.ResultsThe width, thickness and volume of the thyroid decreased gradually before, during and 6 and 12 months after radiotherapy. They were negatively correlated with the mean thyroid dose and V50 (p < 0.05), but were not significantly correlated with the maximum and minimum thyroid doses, V30 and V35 (p > 0.05). The T1WI relative signal intensity (RSI), T2WI RSI, and enhanced T1WI RSI of the thyroid gland gradually decreased from before radiotherapy to during radiotherapy and 6 months and 12 months after radiotherapy. The T1WI RSI, T2WI RSI, and enhanced T1WI RSI during radiotherapy and 6 months and 12 months after radiotherapy were negatively correlated with the mean radiation dose, V40, V45, and V50 of the thyroid gland (p < 0.05), but were not significantly correlated with the maximum radiation dose, minimum radiation dose, V30, and V35 of the thyroid gland or the radiation dose of the pituitary gland (p > 0.05).ConclusionQuantitative MRI analysis can non-invasively and effectively show the changes in thyroid shape, size and signal intensity in patients with nasopharyngeal carcinoma before and after radiotherapy, which is crucial for early and accurate assessment of thyroid damage, enabling timely treatment to preserve thyroid function.